2006
DOI: 10.1002/elan.200603648
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nonsteroidal Anti‐inflammatory Drugs in Serum by Microchip Capillary Electrophoresis with Electrochemical Detection

Abstract: A simple and rapid method has been developed for the analysis of four nonsteroidal anti-inflammatory drugs (NSAIDs) in serum using microchip capillary electrophoresis with pulsed amperometric detection. The selected NSAIDs (salicylic acid, acetaminophen, diflunisal, and diclofenac) are among the most commonly used drugs to treat fever, inflammation, and pain. Used above the therapeutic levels, these drugs can cause a wide variety of adverse effects and their fast analysis could have a significant impact in tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…However, it seems that the serum matrix under acidic conditions enhances the full conversion of DCF to lactam, as DCF-lactam-tms is the sole peak detected in this case, whereas in the absence of serum matrix DCF-tms is detected. The transformation of DCF to DCF-lactam in water samples, pharmaceutical dosage forms, and urine was reported previously but it hasn't been thoroughly studied [11,16]. In a study, DCF-lactam was falsely reported as DCF [20], and in another study DCF-lactam-tms wasn't detected at all [21].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, it seems that the serum matrix under acidic conditions enhances the full conversion of DCF to lactam, as DCF-lactam-tms is the sole peak detected in this case, whereas in the absence of serum matrix DCF-tms is detected. The transformation of DCF to DCF-lactam in water samples, pharmaceutical dosage forms, and urine was reported previously but it hasn't been thoroughly studied [11,16]. In a study, DCF-lactam was falsely reported as DCF [20], and in another study DCF-lactam-tms wasn't detected at all [21].…”
Section: Discussionmentioning
confidence: 95%
“…There are reports of determinations of these analytes by immunoassays, Gas ChromatographyFlame Ionization Detection (GC-FID), High Performance Liquid Chromatography-UltraViolet/Diode Array Detection (HPLC-UV/DAD)/fluorimetric detector, spectrofluorimetry, thin layer chromatography-UV/fluorimetric detector, GC-MS, GC-MS/MS, capillary electrophoresis, LC-MS, and LC-MS/MS [10][11][12][13][14]. Immunoassays suffer from low selectivity due to cross-reactions, while all other methods except LC-MS/MS include time-consuming sample pretreatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylsalicylic acid (ASA) or aspirin, the world's oldest and best known nonsteroidal anti-inflammatory drug, continues to receive special attention due to its clinical effects on inflammation, fever, renal function, and platelet aggregation [1,2]. Recent studies have shown that administrated in specific dosages, aspirin has the ability to prevent cardiovascular events and different types of cancer and to reduce even the incidence of Altzheimer's disease occurence [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, evidence proves that it induces formation of free-radicals which are involved in gastrointestinal damage and development of gastroduodenal ulcer [6][7][8][9]. After entering the bloodstream, acetylsalicylic acid is rapidly metabolized in salicylic acid (SA), the compound known to be primarily responsible for the pharmacological activity of ASA [1,4,10,11]. The therapeutic action and the toxic effects of this widely consumed active substance promote ASA as a drug continuously subjected to extensive research.…”
Section: Introductionmentioning
confidence: 99%